The Conceptual Structure Of Time In The Seven Suspended Odes A Cognitive Linguistic Study/ البنية التصورية للزمن في المعلقات السبع دراسة في ضوء اللسانيات العرفانية - Hani Habeeb; Hazim Dhannoon (Ijaz Arabi Journal of Arabic Learning, 2026)
This study applies Ray Jackendoff’s Conceptual Structure Hypothesis to Arabic linguistic data through the analysis of the Seven Mu‘allaqāt. The study is motivated by the need to diversify theoretical sources in Arabic linguistic research, recognizing that Arabic is a highly creative language. Conceptual structure is not merely a linguistic tool but a fundamental cognitive mechanism that organizes human thought. According to this hypothesis, language and other cognitive faculties operate under a unified system of underlying principles. Conceptual structures are acquired naturally during early childhood, making them epistemologically prior to language, and they can also be observed in certain non-human primates, such as monkeys. The study posits conceptual structure as central to reasoning, inference, and perception, integrating insights from linguistics and cognitive sciences. For practical application, the temporal domain is examined, treating time as a conceptual space. Temporal expressions employ metaphors of movement, trajectory, and spatial extension, including linearity and cyclicity, to represent concepts such as morning, evening, and transitional periods. This analysis demonstrates that the classical Arab intellect was capable of conceptualizing time and transforming it into dynamic and spatially structured visual representations.